How to start a revolution : young people and the future of American politics - Duca, Lauren (Simon & Schuster, 2019)
A columnist at Teen Vogue, Lauren Duca has become a fresh and authoritative voice on the experience of millennials in today's society. Here, she explores the post-Trump political awakening and lays the groundwork for a re-democratizing moment as it might be built out of the untapped potential of young people. Duca investigates and explains the issues at the root of our ailing political system and reimagines what an equitable democracy would look like. It begins with young people getting involved. People like Alexandria Ocasio-Cortez, the youngest woman ever to be elected to Congress; David and Lauren Hogg, two survivors of the Parkland, Florida, shooting who went on to become advocates for gun control; Amanda Litman, who founded the nonprofit organization Run for Something to assist progressive young people in down-ballot elections; and many more.